2022
DOI: 10.1021/acschemneuro.1c00847
|View full text |Cite
|
Sign up to set email alerts
|

Europium-Doped Cerium Oxide Nanoparticles for Microglial Amyloid Beta Clearance and Homeostasis

Abstract: Alzheimer's disease (AD) is the most common neurodegenerative disorder. Pathologically, the disease is characterized by the deposition of amyloid beta (Aβ) plaques and the presence of neurofibrillary tangles. These drive microglia neuroinflammation and consequent neurodegeneration. While the means to affect Aβ plaque accumulation pharmacologically was achieved, how it affects disease outcomes remains uncertain. Cerium oxide (CeO 2 ) reduces Aβ plaques, oxidative stress, inflammation, and AD signs and symptoms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…In contrast, continued scratch growth was observed for conventionally coated samples by phosphate conversion method due to active corrosion. Nevertheless, Ce compounds are known for suppression of oxidative stress and free radical production, which otherwise, could promote several neurodegenerative diseases, such as Parkinson's disease, trauma, ischemic stroke, Alzheimer's disease (AD), and aging [ 96 ]. Recently, Ce based compounds are reported for promoting angiogenesis induction [ 97 ] and peroxidase mimicking activity [ 98 ] for breast cancer cell detection.…”
Section: Coatings and Their Current Statusmentioning
confidence: 99%
“…In contrast, continued scratch growth was observed for conventionally coated samples by phosphate conversion method due to active corrosion. Nevertheless, Ce compounds are known for suppression of oxidative stress and free radical production, which otherwise, could promote several neurodegenerative diseases, such as Parkinson's disease, trauma, ischemic stroke, Alzheimer's disease (AD), and aging [ 96 ]. Recently, Ce based compounds are reported for promoting angiogenesis induction [ 97 ] and peroxidase mimicking activity [ 98 ] for breast cancer cell detection.…”
Section: Coatings and Their Current Statusmentioning
confidence: 99%
“…[ 74 ] Researchers have found that CeO 2 has a potential therapeutic effect on these diseases. [ 75 ]…”
Section: Application For Other Diseasesmentioning
confidence: 99%
“…In particular, CeO 2 induces free radical scavenging and cytoprotective intracellular signaling, which could alleviate the pathobiology of AD‐affected brains. [ 75a ] Machhi et al. synthesized a potential agent of AD immunomodulator: europium‐doped CeO 2 (Eu‐CeO 2 NPs), which increases the phagocytosis and A β ‐degradation ability of cells, so the BV2 inflammatory activity of microglia after A β 1‐42 exposure is attenuated.…”
Section: Application For Other Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the neuroprotective effect of CeO 2 NPs is superior to their other therapeutic capabilities based on their physicochemical properties as nanozymes in reducing radical agents. , Although the protective mechanisms of CeO 2 NPs and their optimum concentrations are still debatable, it has been confirmed that these NPs guide healing or regeneration activities by changing cell polarity from pro-inflammatory to anti-inflammatory phenotype. , In this regard, Ciofani et al using synthesized CeO 2 NPs with dimensions of 5–80 nm containing Ce 3+ and Ce 4+ were able to control the intracellular ROS in order to reduce the apoptosis by reducing Gss and Gpx1 gene expression and increase the neurite length from 55 to 85 μm. Also, they showed that the use of CeO 2 NPs with a concentration of 50 μg/mL increases the expression of β3 tubulin and neurofilaments-66 by 1.5 times .…”
Section: Therapeutic Approaches Of Damaged Pns Based On Metallic Npsmentioning
confidence: 99%